Analisis Perbandingan Kemampuan Kolaborasi Antar Jurusan di Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau - Laila Alvi Syahrina; Nikmah Pajriati; Urfa Ernalia; Jesi Alexander Alim (CV.ITTC INDONESIA, 2025)
Collaboration skills are important skills for students, especially in an academic environment that demands teamwork in problem solving and decision making. This study aims to analyze and compare the collaboration skills of students from several departments at Riau University. The research method used is a quantitative method with data collection techniques using observation, interviews, and questionnaires. The results showed that there were significant differences in students collaboration skills based on factors of academic experience, communication patterns, and the use of team-based learning strategies. Factors that contribute to this difference include curriculum, teaching methods, as well as individual student characteristics. The implications of this study highlight the importance of developing more effective learning strategies to improve students collaboration skills.